Using non-parametric methods to study the differences between factors affecting the weight of newborns - Abdel Hafiz Mohamed, Inas (Iraqi Journal for Administrative Sciences, 2024)
Statistical tests are one of the vital branches of inferential (deductive) statistics, which are analytical statistical methods through which important conclusions are reached about the source from which data were collected and to make the necessary decisions and predict what the phenomenon will lead to in the future. Some of these statistical methods depend on assumptions and conditions and depend on parameters and indicators for a specific type of statistical distributions which are called parameter tests and the other that does not depend on conditions or restrictions and the distribution of data in them is not known called non-parametric tests and the research aims to study the factors affecting the weight of the newborn Using some non-parametric methods in analyzing the two phenomena of diabetes and high blood pressure, and the results were obtained through the application of the Kruskal test wallis. It was found that the factors (mother's age - mother's nutrition level - mother's condition with diabetes and pressure - length Pregnancy) have a significant effect on the weight of the newborn baby and all categories of former number of births